Enhanced corrosion resistance in Fe-based amorphous coatings through eliminating Cr-depleted zones. (15th May 2018) - Wu, J.; Zhang, S.D.; Sun, W.H.; Gao, Y.; Wang, J.Q.
Graphical abstract: Highlights: Localised Cr depletion of Fe-based amorphous coating was analysed via SIMS. The Cr-depleted zones around defects were eliminated by selectively dissolving. The enhancement of corrosion resistance of the coatings was achieved. Abstract: Localised Cr depletion caused by defects in Fe-based amorphous coatings, e.g. pores, oxides and crystalline phases, is thought to be the dominating reason for decreasing corrosion resistance in the coatings. An electrochemical polarisation treatment was used to selectively dissolve Cr-depleted zones in the coatings. The corrosion behaviour of the coatings was studied by potentiodynamic and potentiostatic polarisation and electrochemical impedance spectroscopy in 3.5 wt.% NaCl solution. With the elimination of Cr-depleted zones the corrosion resistance of the coatings was enhanced, with an order of magnitude reduction in the passive current density together with the improvement of passive film stability.